Arrangement Principles of the Busbar Interlocking Joint in Metro Rigid Overhead Catenary System - DAI Hongyu; FENG Chao; SHEN Zhengchao; SANG Guoyang (Chengshi guidao jiaotong yanjiu)
[Objective] The busbar interlocking joints of metro rigid overhead catenary system operate for extended periods within the complex coupled vibration system formed between the pantograph and the contact wire. Improper arrangement of intermediate joints can easily lead to issues such as bolt loosening and joint deformation at the connection points, resulting in hard spots, which can further cause excessive wear of the contact wire and arcing phenomena at the joints. Therefore, it is necessary to study the arranging principle for interlocking joints. [Method] The metro rigid overhead catenary system is modeled as an infinite-span continuous beam, and its bending moment is calculated using the finite element method. The optimal installation positions of interlocking joints under different standard span lengths are analyzed. Based on various standard lengths of busbar, the optimal arrangement scheme of interlocking joints within a standard anchoring section is proposed. Additionally, the influence of different installation positions of interlocking joints on the deflection of busbar and the dynamic characteristics of the structure is analyzed. [Result & Conclusion] To ensure a favorable stress condition at the interlocking joints, it is recommended to match the standard span length with the corresponding busbar length, thereby ensuring that all interlocking joints within the anchoring section are installed near the zero-bending-moment points of busbar. The installation position of interlocking joints within a span has a certain impact on the mid-span deflection of busbar, while its influence on the overall structural dynamic characteristics of the anchoring section is negligible.